Quantifying and improving the optical performance of the laser ablation aerosol particle time of flight mass spectrometer (LAAPToF) instrument. Issue 7 (2nd July 2020) - Zawadowicz, Maria A.; Lance, Sara; Jayne, John T.; Croteau, Philip; Worsnop, Douglas R.; Mahrt, Fabian; Leisner, Thomas; Cziczo, Daniel J.
Abstract: Single particle mass spectrometer (SPMS) instruments have been used for in-situ chemical characterization of atmospheric aerosols, both in the field and laboratory, for over two decades. SPMSs typically combine precise optical particle sizing with laser desorption and ionization followed by time of flight mass spectrometry. Among the advantages of SPMSs over other aerosol chemistry measurement techniques are their single particle resolution and high sensitivity to trace chemical species. The AeroMegt Laser Ablation Aerosol Particle Time of Flight Mass Spectrometer (LAAPToF) is a commercially available member of this instrument class, aiming for a compact size and simplicity for the end user. This article quantifies the performance of LAAPToF with an emphasis on optical counting efficiency. Recommendations for improving detection compared to the base LAAPToF hardware are described. Our results show that changes to the optical detection scheme can lead to over two orders of magnitude improvement in optical counting efficiency in the size range 500–2000 nm vacuum aerodynamic diameter. We also present mass spectral performance for characterizing atmospherically relevant particles in a comparison to a current SPMS design, the Particle Analysis by Laser Mass Spectrometry. Copyright © 2020 American Association for Aerosol Research